Students’ Perceptions of Using the Word Search Puzzle Game in English Club - Hery Kiswanto; Elsayed Mohamed Salem Salem Elawadi (English Education Department, 2026)
This study aims to investigate students’ perceptions of using the Word Search Puzzle Game in the English Club. The background of this research is based on the need for engaging learning media to increase students’ interest and motivation in learning English, especially in extracurricular activities such as the English Club. This research employed a descriptive quantitative survey design. The population of this study consisted of 184 students from second grade to sixth grade who participated in the English Club at SDS IT Mutiara Pinggir. Using the Slovin formula, 126 students were selected as the sample of the research. The data were collected through a questionnaire using a four-point Likert scale consisting of strongly agree, agree, disagree, and strongly disagree. The data were analyzed using descriptive statistics, including mean, percentage, and mode. The findings of this study show that students have highly positive perceptions of the use of the Word Search Puzzle Game in English Club activities. The results indicate that all perception indicators usefulness, enjoyment, motivation, and engagement obtained mean scores above 3. In addition, more than 93% of respondents selected “agree” or “strongly agree,” and the mode value for most items was 4. These findings demonstrate that students perceive the Word Search Puzzle Game as useful, easy to use, enjoyable, and effective in increasing their motivation and engagement during English Club activities. In conclusion, the Word Search Puzzle Game is an effective interactive learning in English Club activities at the elementary school level.